Лепная керамика вельбарско-пшеворского типа в черняховских древностях Днепро-Донецкой Лесостепи - Дидык, В.В. (My University, 2005)
V. Didyk. Plastic Ñeramics of Ìelbarsko-pshevorskogo Eype in Chernyakhovsky Antiquity in Dnepro-Donetsk Wood Steppe Publication is devoted to analysis and classification of plastic ceramics of velbarskopshevorskogo type, which was discovered in chernyakhovsky artefacts in Dnepro-Donetsk wood steppe. Four groups of pots (1A–1D) and 10 groups of kitchenware as per R. Wologiewich’s formal typology have been distinguished. Analysis of plastic ceramics and ornaments allows preliminary to mark distinctions between Pravoberezhnaya Ukraine and Dnepro-Donetsk wood steppe velbarsko-pshevorskogo ceramics.